SUBAK AS A MODEL OF BALI’S FOOD SECURITY BASED ON LOCAL WISDOM AND TRI HITA KARANA - I Wayan Arya Adnyana (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2026)
This article examines the sustainability of the Subak system as a model of Bali’s food security grounded in local wisdom and the philosophy of Tri Hita Karana. Subak is not merely a traditional irrigation system, but a socio-religious institution that integrates ecological management, social organization, and spiritual values. This study employs a qualitative literature review method by analyzing ten national and international scholarly articles discussing Subak from ecological, socio-cultural, economic, and institutional perspectives. The findings indicate that Subak faces multidimensional challenges, including agricultural land conversion, weakening social cohesion, institutional limitations, and a crisis in farmer regeneration. Nevertheless, the literature also highlights significant opportunities for preservation through strengthening Tri Hita Karana values, reinforcing customary institutions, developing sustainable tourism, diversifying agribusiness, integrating digital technology, and enhancing policy support. Through an integrated and collaborative strategy, Subak can be preserved not only as cultural heritage but also empowered as an adaptive agrarian system capable of sustaining Bali’s food security in the era of globalization.